Lipoleiomyoma of the left broad ligament with dermoid cyst in ipsilateral ovary and synchronous multiple benign lesions of female genital tract: An unusual association - Sweta Singh Mishra; Arpita Saha; Pritinanda Mishra; Saubhagya Kumar Jena (Wolters Kluwer Medknow Publications, 2016)
Lipoleiomyoma of the uterus is a rare variant of leiomyoma, and lipoleiomyoma of the broad ligament is still rarer, with only a handful of cases being reported. The present case was a perimenopausal woman who presented with a huge lower abdominal mass. Ultrasonography and computed tomography showed a heterogeneous solid mass in the left adnexa. The histopathological findings confirmed the nature of the lesions as a benign lipoleiomyoma with dermoid cyst of the left ovary and its other associated benign lesions, were the interesting features seen in this case which were not suspected clinically and radiologically.